Enhanced flux pinning in YBCO multilayer films with BCO nanodots and segmented BZO nanorods. Issue 1 (December 2017) - Malmivirta, Mika; Rijckaert, Hannes; Paasonen, Ville; Huhtinen, Hannu; Hynninen, Teemu; Jha, Rajveer; Awana, Veerpal; Driessche, Isabel; Paturi, Petriina
Abstract The flux pinning properties of the high temperature superconductor YBa2 Cu3 O7−δ (YBCO) have been conventionally improved by creating both columnar and dot-like pinning centres into the YBCO matrix. To study the effects of differently doped multilayer structures on pinning, several samples consisting of a multiple number of individually BaZrO3 (BZO) and BaCeO3 (BCO) doped YBCO layers were fabricated. In the YBCO matrix, BZO forms columnar and BCO dot-like defects. The multilayer structure improves pinning capability throughout the whole angular range, giving rise to a high critical current density, J c . However, the BZO doped monolayer reference still has the most isotropicJ c . Even though BZO forms nanorods, in this work the samples with multiple thin layers do not exhibit ac axis peak in the angular dependence ofJ c . The angular dependencies and the approximately correct magnitude ofJ c were also verified using a molecular dynamics simulation.